Towards a global translatological approach based on the noun - MALEK, Yacine (Journal of Human Sciences, 2020)
This study undertakes to demonstrate that today’s translatology comes under an epistemological translation, whereas it should deal with an ontological translation. Therefore, it will examine the signified and what it implies as notions of signification and sense, and will attempt to explain the logical verisimilitude of the context, but also its nature, which should not exist as part of the aforementioned ontological translation. Subsequently, it will be a question of establishing the theoretical principles of a new noun-based translatological approach after having demonstrated that it (the noun) would be the holosemantic part of discourse. The study qualifies this approach as global because it represents an overview by which it will be necessary to explain the possibility of uniting signification and sense in spite of the “onto-logical” improbability of the latter.